PENERAPAN EIGENFACE UNTUK COMPUTER BASED TEST (CBT) PENERIMAAN MAHASISWA BARU SEKOLAH TINGGI TEKNOLOGI ADISUTJIPTO - Haruno Sajati; Astika Ayuningtyas; Dwi Kholistyanto (Compiler, 2017)
One of the development of computer technology is the availability of systems or applications that help human work everyday so that can be resolved quickly and correctly. The system, one of which is Computer Based Test (CBT). CBT is an application used for tests conducted using computers that are in the application there are some features of CBT security when working on the problem. CBT can use a stand-alone computer, a computer connected to a network or a computer connected to the internet. Facial recognition is a type of biometric application that can identify specific individuals in a digital image by analyzing and developing face patterns. In its implementation, CBT has a weakness in the security system that becomes the gap of CBT users to commit fraud, therefore required a good security system with the creation of CBT applications that use eigenface algorithm. It is necessary to have a security system that overcomes the problem that is required identification of face recognition of participants during the test so that cheating can be reduced. The results of the test using eigenface algorithm accuracy rate reached 82%, some things that affect the level of accuracy is, the intensity of light, facial position and the use of accessories on the face.